The impact of Appleton's model on the development of reflective thinking among students of the Institute of Fine Arts in art criticism (Journal of the College of Basic Education, 2023)
Summary of the research :The research seeks to demonstrate the impact of Appleton's model in developing reflective thinking among the students of the Institute of Fine Arts in the subject of art criticism. For the subject of art criticism, the research sample consisted of (26) students as an experimental group, and to reach the results of the research, the two research tools were a cognitive achievement test and a measure of reflective thinking. In light of the results of the research, the researcher concluded: Teaching according to the Ableton model has an impact on the development of reflective thinking among students of the Institute of Fine Arts in the subject of art criticism. The most important thing recommended by the researcher: working to increase the interest in modern teaching models that help to achieve the mental abilities of students, and the most important proposals suggested by the researcher: conducting a similar study to find out the impact of Ableton's model in solving problems.Keywords: Ableton model - development of reflective thinking - art criticism.